A Community Marine Tourism as a Business Sector: Challenges Faced by Local Community - Adi Suryani; Soedarso Soedarso; Deti Rahmawati; Moh. Saifulloh; Dyah Satya Yoga Agustin (International Journal of Business Studies, 2022)
Marine tourism is one of several economic drivers which contribute to local community livelihood and regional income. Many potential coastal areas are gradually developing and transformed by its’ local communities into local-scale tourisms which accommodate local or domestic or surrounding tourists’ recreational needs. However, to be sustainable, there are many issues need to be addressed. The study intends to explore Dalegan community perceived tourism issue in developing their WPP destination or white sand tourism. The study adopts qualitative method in gathering and analyzing the data. The data are gathered through Dalegan community dialog or interactive session during Dalegan community service program. The collected data are interpreted by implementing thematic analysis. The study reveals that there are three main issues faced by Dalegan local communities: financial, creativity and lack of legal procedures. The collaboration of financial service agents, educational institutions, (local) government bodies and local community inclusion is needed. The study demonstrates that to build Dalegan marine tourism, local/community leadership, local human quality improvement, local resources identification and local culture need to be used as the development grounds. The study also shows that the local community is still not aware of the environmental issues and diversification of recreational activities. Thus, local community still needs advocacy to understand the relationship between tourism and environment. The study also finds that local women are valuable human resource for marine tourism business. They are potential women entrepreneurs who develop small business around WPP marine tourism.